FUNGSI HAK ANGKET DEWAN PERWAKILAN RAKYAT UNTUK MELAKUKAN PENYELIDIKAN TERHADAP PELAKSANAAN UNDANG-UNDANG - Sumartini, Siti; Arifin, Jajang (Universitas Wiralodra, 2020)
The inquiry right of the House of Representatives (DPR-Dewan Perwakilan Rakyat) is the right of the DPR to conduct an investigation of the implementation of laws/government policies relating to important things, strategic, and broad impacts on the life of the community, nation, and state suspected of being in conflict with the law regulations. The DPR's inquiry rights relating to the implementation of the DPR's oversight function are â€œan institutionalized system, involving the effectiveness and regularity of restrictions on government actionsâ€. According to the definition above, the questions arise is what is the position of the inquiry rights in the implementation of the DPR's oversight function on the implementation of a law? What is the implication of the Constitutional Court's decision Number: 36 / PUU-XV / 2017 for the implementation of the DPR's inquiry right to the Corruption Eradication Commission (KPK â€“ Komisi Pemberantasan Korupsi)? The study was conducted using a normative juridical approach (legal research). In this case, testing and reviewing secondary data are done relating to the problem to be discussed. The inquiry right is not the right to know about the possibility of a crime in a case. The inaccuracy in the conception of the inquiry right which is also shown in its implementation such as the DPR investigating the Bullogate, BLBI cases and others can (even) distort the function of the DPR in the formation of laws (legislation) or oversight of the implementation of government tasks and state spending, including the appointment of public officials in the form of public officials, approval or rejection, or in the form of giving consideration by the Parliament. Therefore, if the function is expected to be carried out effectively, dynamically, and naturally, changes to the MD3 Law must be initiated primarily by members of the DPR itself. There must be a strong desire from the members of Parliament to reposition themselves as representatives of the people who are aspirational and serve the interests of all the people they represent. This strong desire will manifestly manifest, if they are not restarted, because they are opposing the party's policy line.